The State of Music Therapy Studies in the Past 20 Years: A Bibliometric Analysis - Li, Kailimi; Weng, Linman; Wang, Xueqiang (Frontiers in Psychology, 2021)
Purpose: Music therapy is increasingly being used to address physical, emotional, cognitive and social needs of individuals. However, publications on the global trends of music therapy using bibliometric analysis are rare. The study aimed to use CiteSpace software to provide global scientific research about music therapy from 2000 to 2019. Methods: The publications related to music therapy were searched between 2000 and 2019 from the Web of Science (WoS) database. CiteSpace V software was applied to perform co-citation analysis about authors, and visualize the collaborations between countries or regions into a network map. The linear regression was applied to analysis the overall publication trend. Results: A total of 1,004 papers met the inclusion criteria in this study. These works were written by 2,531 authors from 1,219 institutions. The results revealed that music therapy publications had a significant growth over time, because the linear regression results revealed that the percentages had a notable increase from 2000 to 2019 (t = 14.621, P < 0.001). The USA had the largest number of published papers (362 publications), along with the following outputs: citations in WoS (5,752 citations), citations per paper (15.89 citations), and a high H-index value (37). The three keywords “efficacy,” “health,” and “older adults” emphasized the research trends in terms of the strongest citation bursts. Conclusions: The overall trend of music therapy is positive. The findings provide useful information for music therapy researchers to identify new directions related to collaborators, popular issues, and research frontiers. The development prospects of music therapy could be expected and future scholars could pay attention to the clinical significance in music therapy to improve people’s quality of life.